2003
DOI: 10.1111/j.1346-8138.2003.tb00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Stress, Stress Perception and Trait‐Anxiety in the Onset and Course of Alopecia Areata

Abstract: Clinical observations suggest that the nervous system, including psychological factors, can influence the onset and course of alopecia areata (AA). The aim of this study was to determine whether stressful life events, stress perception, and trait-anxiety are risk factors in the onset and course of AA. A group of 45 patients diagnosed with AA and a group of 45 healthy controls were participants in the study. The patients with AA were divided into two subgroups: patients with a first episode of AA and patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 17 publications
1
57
1
6
Order By: Relevance
“…However, a study by Brajac in 2003. 8 was unable to establish causal relationship between alopecia areata with stressful life events. 8 Positive family history of alopecia was given by 51% subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study by Brajac in 2003. 8 was unable to establish causal relationship between alopecia areata with stressful life events. 8 Positive family history of alopecia was given by 51% subjects.…”
Section: Discussionmentioning
confidence: 99%
“…8 was unable to establish causal relationship between alopecia areata with stressful life events. 8 Positive family history of alopecia was given by 51% subjects. Twin studies in males indicate that susceptibility, age of onset, pattern and rate of progression of male pattern baldness are under genetic influence.…”
Section: Discussionmentioning
confidence: 99%
“…Finally hair follicles are both sources and targets of CRF/Ucn 1 lineage peptides with resulting effects on pigmentation [122,138]. Thus, it has been suggested that disorders such as atopic dermatitis, psoriasis [270], alopecia areata [31,136], and chronic urticaria [200] involve a stress-related precipitation or exacerbation of skin mast cell activation (and possibly other resident skin cells) via local CRF/Ucn 1-CRF receptor signaling.…”
Section: 45mentioning
confidence: 99%
“…Sin embargo, en la AA estas evidencias han sido circunstanciales (43). Hay autores que muestran relación entre estrés y AA (8,44), y otros que no le conceden significación (45). Existe un volumen importante de trabajos que se ocupa del estrés psicosocial como desencadenante de los brotes.…”
Section: Comienzo De La Enfermedadunclassified